Sentiment analysis of telecom official micro-blog users based on LSTM deep learning model - Xin CAI; Jingsheng LOU (Dianxin kexue)
As an internet media,China Telecom official micro-blog is an important channel for the company to publish information and get feedback from users.Users’ comments on telecom official micro-blog messages reflect different attitudes towards telecom brand,products and services.The message content and comment data of the micro-blog was crawled,and the Word2vec was used to express the text information after data cleaning,and the deep learning platform was chosen to carry out the positive and negative emotional classification of the user interaction text based on the LSTM deep neural network model,and sentiment analysis of telecom official micro-blog users was realized.